The relationship between education level, retirement status, and civic engagement among older adults in Indonesia - Winata, I Komang (Universitas Negeri Yogyakarta, 2021)
The Indonesian population is aging very rapidly and as the number of old people increases, the number of retirees increases as well. Many scholars have argued the benefits of civic engagement in old age, but there is lack of empirical evidence of the factors associated with civic engagement in Indonesia. The aim of this study was to investigate the association between education levels, retirement status, and civic engagement among older adults in Indonesia. The study used data from the fifth wave of the Indonesia Family and Life Survey which was held in late 2014 and early 2015. The study included participants aged 56 years and older, the mandatory age for retirement in 2014 in Indonesia. Multiple regression was modelled for data analysis. The main results revealed that those who completed junior and senior high school and high education exhibited more civic engagement than those who completed only primary education. Moreover, the study found that those who were retired were less engaged in civic activities than those still in labor force. These relationships held true even after controlling for gender, age, marital status, personality traits, religiosity, and self-rated health variables. To strengthen democracy and growth, education needs to be re-emphasized and there is need for further investigation concerning retirement and civic engagement in Indonesia.